Implementation of Congregational Dzuhur Prayer Activities in Improving Religious Character for Grade VI Students in Elementary Schools - Fitri, Rika; Rahman, Ikhwan; Satria, Rachmat (Khalaqa: Journal of Education and Learning, 2024)
Some sixth-grade students still do not participate in the congregational Dzuhur prayer. When the teacher encourages them to join the prayer, these students ignore the instruction—some go to the school canteen, while others leave the school premises. This study aims to describe the implementation of congregational Dzuhur prayer activities as a means of instilling religious character in elementary school students. The research employs a qualitative method with a descriptive approach. Data collection techniques include observation, interviews, and documentation. The research informants are Islamic Religious Education teachers and the school principal, selected through observation, interviews, and documentation. The collected data were analyzed using qualitative analysis procedures, which consist of data reduction, data presentation, conclusion drawing, and verification. To ensure data validity, the study uses source and technique triangulation. The findings reveal that congregational Dzuhur prayer activities have a significant impact on shaping students’ spiritual character. Students require not only broad knowledge and insight but also a deeply rooted religious and spiritual foundation. These prayer activities contribute meaningfully to the development of that foundation.